Trace element landscape of resting and activated human neutrophils on the sub-micrometer level1. Issue 6 (10th June 2015) - Niemiec, M. J.; De Samber, B.; Garrevoet, J.; Vergucht, E.; Vekemans, B.; De Rycke, R.; Björn, E.; Sandblad, L.; Wellenreuther, G.; Falkenberg, G.; Cloetens, P.; Vincze, L.; et al.
<x xml:space="preserve">Abstract</x> Neutrophils and extracellular traps examined by synchrotron radiation X-ray fluorescence and inductively coupled plasma mass spectrometry.